Resiliensi Usaha MIkro, Kecil, Menengah (UMKM) dan Kebijakan Pemerintah di Masa Pandemi Covid 19 - Dewi Amaliah Nafiati Raharjo; Endang Sri Mulyani (Jurnal Utilitas, 2020)
Micro, Small, and Medium Enterprises (MSMEs) are businesses that play an important and strategic role as a stabilizer and dynamics of economic development in Indonesia. UMKM resilience also has tested when Indonesia experienced a monetary crisis in 1997. Currently, Indonesia is experiencing a crisis again caused by the COVID pandemic 19. The COVID 19 pandemic crisis has had a significant impact on the sustainability of MSME. Almost all MSMEs suffer losses, have difficulty running their operational activities, and even have to close down their businesses because their products cannot be absorbed by the market. This condition is again testing the resilience of MSMEs to be able to deal with the 19th COVID pandemic crisis. Various strategies have been developed to get out of this crisis. Among others by optimizing the online-based sales system that utilizes a variety of marketplace platforms to market their products. The role of the government is very important to help MSMEs to be strong in facing the COVID pandemic crisis 19. Monetary policies such as relaxation of loans, delaying installments and interest on loans as well as social assistance are a breath of fresh air for MSMEs to be able to breathe a little between the crush of the COVID pandemic crisis 19.